Single nucleotide polymorphisms in an intergenic chromosome 2q region associated with tissue factor pathway inhibitor plasma levels and venous thromboembolism. (17th September 2016) - Dennis, J.; Truong, V.; Aïssi, D.; Medina‐Rivera, A.; Blankenberg, S.; Germain, M.; Lemire, M.; Antounians, L.; Civelek, M.; Schnabel, R.; Wells, P.; Wilson, M. D.; et al.
Abstract : Essentials Tissue factor pathway inhibitor (TFPI) regulates the blood coagulation cascade. We replicated previously reported linkage of TFPI plasma levels to the chromosome 2q region. The putative causal locus, rs62187992, was associated with TFPI plasma levels and thrombosis. rs62187992 was marginally associated with TFPI expression in human aortic endothelial cells. Click to hear Ann Gil's presentation on new insights into thrombin activatable fibrinolysis inhibitor Summary: Background: Tissue factor pathway inhibitor (TFPI) regulates fibrin clot formation, and low TFPI plasma levels increase the risk of arterial thromboembolism and venous thromboembolism (VTE). TFPI plasma levels are also heritable, and a previous linkage scan implicated the chromosome 2q region, but no specific genes. Objectives: To replicate the finding of the linkage region in an independent sample, and to identify the causal locus. Methods: We first performed a linkage analysis of microsatellite markers and TFPI plasma levels in 251 individuals from the F5L Family Study, and replicated the finding of the linkage peak on chromosome 2q (LOD = 3.06). We next defined a follow‐up region that included 112 603 single nucleotide polymorphisms (SNPs) under the linkage peak, and meta‐analyzed associations between these SNPs and TFPI plasma levels across the F5L Family Study and the Marseille Thrombosis Association (MARTHA) Study, a study of 1033 unrelated VTE patients. SNPs with false discovery rate q ‐values of < 0.10 were tested for association with TFPI plasma levels in 892 patients with coronary artery disease in the AtheroGene Study. Results and Conclusions: One SNP, rs62187992, was associated with TFPI plasma levels in all three samples ( β = + 0.14 and P = 4.23 × 10 −6 combined; β = + 0.16 and P = 0.02 in the F5L Family Study; β = + 0.13 and P = 6.3 × 10 −4 in the MARTHA Study; β = + 0.17 and P = 0.03 in the AtheroGene Study), and contributed to the linkage peak in the F5L Family Study. rs62187992 was also associated with clinical VTE (odds ratio 0.90, P = 0.03) in the INVENT Consortium of > 7000 cases and their controls, and was marginally associated with TFPI expression ( β = + 0.19, P = 0.08) in human aortic endothelial cells, a primary site of TFPI synthesis. The biological mechanisms underlying these associations remain to be elucidated.